Determining Sales Patterns Using the Apriori Algorithm: A Case Study of Unlocked Cafe's Website Applications - Rafika Sari; Nur Helmy; Allan Desi Alexander (LPPM Universitas Islam 45 Bekasi, 2024)
In the business world, the sales process is the key to a company's success. Business processes will involve a lot of transaction data which will increase over time. This accumulation of data will not provide meaningful information if it is not processed and utilized properly. Correct decision making is obtained from accurate and informative data. This research was conducted to analyze, simulate and digitize data in the form of a website-based system which can be used as recommendations in making business decisions. The application of the Apriori algorithm supports system development in determining sales patterns by providing an overview of sales patterns for products of interest so that sales association rules are obtained. This research dataset was taken from transactions at the Unlocked Café & Coffee shop. The result of this research is an application designed according to the needs of business owners in the form of selecting itemsets by applying the Apriori algorithm to produce output in the form of product stock reference data and product sales patterns.